Faktor yang Mempengaruhi Minat Beli Roti Halal pada Mahasiswa Muslim - Hanum, Fauziyyah; Adityawarman, Adityawarman (Universitas Islam Negeri Sunan Kudus, 2020)
Public consumption of bread has increased because bread is considered practical, easy to find, and can be consumed at any time so that makes buying interest in bread continues to increase. However, bread has a critical point in the additional ingredients used in making bread so that its halalness is still in doubt. Based on this phenomenon, the purpose of this study is to find out the factors that influence the buying interest of Muslim Consumers in halal bread products. This research uses a quantitative method with Multiple Linear Regression analysis which is assisted by using SPSS software version 23. Independent variables in this study are halal awareness, halal certification, religiosity, halal marketing, and personal social perception. While the dependent variable is purchase intention. Data obtained through a questionnaire distributed to 100 Muslim students of the Faculty of Economic and Busines , Diponegoro University, Semarang. The results of the study showed that halal awareness, halal certification, religiosity, halal marketing, and personal social perception affected the purchase intention of halal bread positively and significantly.